The secret soldier - Berenson, Alex. (New York : Jove Books, 2012)
CIA operative John Wells goes undercover in Saudi Arabia and Lebanon to find conspirators bent on tearing down the monarchy of King Abdullah. If the conspirators prevail, it will mean more than just the fall of a monarch -- it may be the start of a final conflagration between America and the full force of Islam itself.
Includes a special excerpt from The shadow patrol (p. [499]-517).
Keywords: United States. -- Central Intelligence Agency -- Fiction; Wells, John (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Saudi Arabia -- Fiction; Spy stories; Suspense fiction